FLEXIBLE WORKING HOURS DURING THE PANDEMIC - TOMESCU-DUMITRESCU CORNELIA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2023)
In order to survive and develop, organizations need to create structures able to anticipate tendencies of economic and social evolution. Therefore, the strategic planning of the organization, the human resources included, represents the most important managerial activity of long run effects. Sadly, the Covid-19 pandemic changed and continues to change the human resources organization. Thus, the organization itself has to assess permanently. The organization needs to assess its own structure, the efficiency of the information and resources, the ability of the organization’s adjustment to the external conditions. The organization has to assess the personnel’s abilities to make use of the new technologies, the capacity of investing in improving and retraining the personnel etc.